Products with vegetable pulp: an alternative for civil engineering: Alternativa de sostenibilidad: materiales con Celulosa - Monroy Gutierrez, Jackson Erminzul; Diaz Ochoa, Martha Liliana; Vera Guarnizo, Maria Claudia (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The population increase has generated urban development in the different cities consuming natural resources at an accelerated pace, generating a devastating environmental impact, which is inevitable because construction is vital for progress in all countries. Consumption on construction sites generates a shortage of renewable raw materials, in addition to the fact that traditional materials such as clay masonry generate energy and contaminant consumption, which is why the world of construction must be transformed to generate sustainable development. Due to the above, the use of vegetable cellulose as a raw material to mitigate the environmental impact and its use in different construction products is analyzed as a sustainable alternative